Pengembangan Media Pembelajaran Berbasis Microsite Materi Perubahan Dan Pelestarian Lingkungan Hidup (Penelitian Di SMA Negeri 1 Paguyaman): (Development of Microsite-Based Learning Media Materials Change And Preservation of The Environment (Research In SMA Negeri 1 Paguyaman)) - Ibrahim, Darwin; Lamangantjo, Chairunnisah J.; Ibrahim, Mustamin; Latjompoh, Masra; Baderan, Dewi Wahyuni K.; Mardin, Herinda (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2025)
This study aims to describe 1). Validity of microsite learning media. 2). The practicality of microsite learning media, and 3) analyzing student learning outcomes. The research used a limited test on 20 respondents in class X.E in the even semester of SMA Negeri 1 Paguyaman for the 2024/2025 school year. The type of development research uses the ADDIE model. The results of the research showed that the validity of the media was 92.41% (very valid), the validity of the material was 89.47% (very valid), and the validity of the questions was 91.42% (very valid). The practicality test consisted of a teacher response of 95.5% (very practical) and a student response of 92.76% (very practical). The student learning outcome test was obtained from the results of the pretest and posttest evaluation, which was then analyzed using N-Gain, obtaining an average score of 0.41 (moderate). Based on the results of the description of all the percentage values, it shows that